Assessing integrated watershed management and spatial groundwater vulnerability to pollution in priority watersheds of the Yacyretá dam in Paraguay - Musálem Castillejos, Karim (CATIE, Turrialba (Costa Rica). University of Wales, Bangor (RU), 2014)
Tesis (Ph.D.) - CATIE, Turrialba (Costa Rica), 2010